ANALISIS GAYA KOGNITIF FIELD DEPENDENT DAN FIELD INDEPENDENT TERHADAP PENGUASAAN KONSEP FISIKA SISWA KELAS VII - Muhamad Gina Nugraha; Santy Awalliyah (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Each student has different characteristics in processing the information (cognitive style), including how to respond, and execute information in learning process to become a useful skills for themselves. This study aims to analyze the differences in cognitive styles of students, namely field dependent and field independent cognitive style towards mastery of concepts. The study was conducted in one of the SMP Negeri Bandung with a sample of 74 students selected by nonrandom sampling method, consisting of 36 students with field dependent cognitive style, and 38 students with field independent cognitive style. All samples do the same learning process (discussions and experiments in groups). Mastery of the concepts of physics obtained by instrument test that has been validated and tested, while the students' cognitive style classification is determined using standard instruments Group Embedded Figure Test (GEFT). The result showed that students with field dependent cognitive style increased mastery of concepts with n-gain of 0.27, while students with field independent cognitive style increased mastery of concepts with n-gain 0.23. Based on the research results, mastery concepts for field dependent students slightly larger than field independent students, it is predicted because of the learning process tend to be clustered so that more support dependent cognitive style. Keywords: field dependent, field independent, mastery concept.